2018
DOI: 10.14218/jcth.2018.00030
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-1 Anti-trypsin Exerts a Hepatoprotective Effect on Immune-mediated Hepatitis and Acetaminophen-induced Liver Injury

Abstract: Background and Aims: The serine proteinase inhibitor alpha-1 anti-trypsin (AAT) protects the body against protease activity. Several functions of AAT beyond those attributed to its anti-protease activity have been described, among them immunomodulatory and anti-inflammatory properties. The present study aimed to determine the efficacy of AAT for the treatment of immune-mediated liver injury using the models of concanavalin A-induced immune-mediated hepatitis and acetaminophen -induced liver damage.Methods: AAT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
0
0
0
1
Order By: Relevance
“…[14] While not explored in this study, Yehudit Shabat et al showed that treatment with alpha-1 anti-trypsin, a serine protease inhibitor that limits neutrophil elastase activity, exerts a hepatoprotective effect on animal models of immune-mediated hepatitis and acetaminophen-induced liver damage. [49] Therefore, adjunct therapies aimed at other facets of NETs could offer additional protection following cholestasis.…”
Section: Discussionmentioning
confidence: 99%
“…[14] While not explored in this study, Yehudit Shabat et al showed that treatment with alpha-1 anti-trypsin, a serine protease inhibitor that limits neutrophil elastase activity, exerts a hepatoprotective effect on animal models of immune-mediated hepatitis and acetaminophen-induced liver damage. [49] Therefore, adjunct therapies aimed at other facets of NETs could offer additional protection following cholestasis.…”
Section: Discussionmentioning
confidence: 99%
“…Результати наших досліджень підтверджуються даними літератури про те, що під час токсичного ураження печінки визначення активності амінотрансфераз інформативно показує зміну проникності клітинних мембран гепатоцитів [13]. Ми відмітили значне зростання активності АлАТ (табл.…”
Section: результати та їх обговоренняunclassified